Does Welfare Policy Affect Residential Choices? Evidence from a Natural Experiment - Jon H. Fiva (Statistics Norway, Research Department, 2007)
This paper studies how changes in welfare benefit levels affect welfare recipients' residential choices. Although several empirical studies have stressed that welfare policy may affect residential choices of welfare recipients, few studies have simultaneously taken into account that residential choices of welfare recipients also affect welfare policy. The main contribution of this paper is to address this policy endogeneity by utilizing a policy reform as a natural experiment. The results show that welfare policy exerts a nontrivial effect on residential choices of welfare recipients. Moreover, I show that ignoring the policy endogeneity may give rise to a downward bias in the estimated migration responses.
Keywords: I38; H73; H77; R23; 330; Welfare Benefits; Migration; Policy Endogeneity